Hubungan Penguasaan Fungsi Kalimat Dengan Kemampuan Menulis Karangan Pada Siswa Kelas VIII SMP Negeri 2 Sosa - Hapsyah Hasibuan (Jurnal Sinar Edukasi, 2020)
The purpose of this study is to find out whether there is a signficant relationship between the mastery of sentence functions with the ability to write essays in Class VIII students of SMP Negeri 2 Sosa. The method used by the author to carry out this research is descriptive method. The population of this research is all students of Class VIII of SMP Negeri 2 Sosa in the 2014/2015 Academic Year, amounting to 214, in which all students are divided into six classes. The sample of this study was taken using cluster sample techniques of 35 students. The instrument used by the authors to collect data is a test. To analyze the data, the authors used descriptive techniques and statistical analysis techniques, namely the Product Moment by Pearson approach. Descriptive analysis results showed the mean value of students of Class VIII of SMP Negeri 2 Sosa was 64.43. That is, the mastery of student sentence functions is still in sufficient criteria. Furthermore, the value of students in writing essays is 66.57. That is, the ability to write student essays is still in sufficient criteria. The results of statistical analysis show that the research hypothesis can be accepted, where the value rxy is greater than the value rt or 0.953 > 0.344. So, there is a signficant relationship between the mastery of sentence functions with the ability to write essays in Class VIII students of SMP Negeri 2 Sosa.